Pengembangan Media Pembelajaran Articulate Storyline 360 Pada Mupel Ipas Kelas IV SDN 2 Trucuk Klaten - B. Wiranto, B. Wiranto; K. Bektiningsih, K. Bektiningsih (Universitas Pakuan, 2025)
DEVELOPMENT OF ARTICULATE STORYLINE 360 LEARNING MEDIA IN GRADE IV SCIENCE MUPEL AT SDN 2 TRUCUK KLATENEducation is important for someone to live their life in the future. Nowadays, learning often uses learning media as a means of conveying material to students, but there are also teachers who have not been able to use these facilities optimally. During the implementation of science and science learning at SDN 2 Trucuk, the teacher had not utilized the facilities for learning media so that students' interest in learning was low and resulted in students' learning outcomes being less than optimal. The aim of this research is to develop Articulate Storyline 360 learning media on cultural diversity and local wisdom material to improve student learning outcomes in class IV SDN 2 Trucuk Klaten. This research uses the Research and Development method and the ADDIE model. The research instruments used were questionnaires and tests as well as data collection methods through observation, interviews and tests. The data analysis technique used is qualitative and quantitative descriptive analysis. The subjects in this research are teachers, students, media experts and material experts. The results of this research are that student learning outcomes have increased significantly and the Articulate Storyline 360 learning media is feasible. used and effective in implementing learning to improve student learning outcomes.